Genital—Systemic Chemokine Gradients and the Risk of HIV Acquisition in Women. (1st March 2017) - Liebenberg, Lenine J. P.; Masson, Lindi; Arnold, Kelly B.; Mckinnon, Lyle R.; Werner, Lise; Proctor, Elizabeth; Archary, Derseree; Mansoor, Leila E.; Lauffenburger, Douglas A.; Abdool Karim, Quarraisha; Abdool Karim, Salim S.; Passmore, Jo-Ann S.
Abstract : Background: Mucosal and systemic immune mediators have been independently associated with HIV acquisition risk, but the relationship between compartments remains unclear. Methods: To address this, the concentrations of 12 cytokines were compared in matched plasma and cervicovaginal lavages (CVLs) from 57 HIV-positive women before their acquisition of HIV (cases) and 50 women who remained uninfected (controls) during the CAPRISA 004 trial. Results: Although genital IP-10 concentrations were significantly higher in cases, plasma IP-10 concentrations were inversely associated with HIV risk. Comparing differences in mucosal and systemic cytokine concentrations between cases and controls, mucosa-biased gradients indicating higher cervicovaginal lavage relative to plasma concentrations were observed for all 5 chemokines in the panel. Four were significantly associated with HIV acquisition, including IP-10 (odds ratio [OR] 1.73, 95% confidence interval [CI]: 1.27 to 2.36), macrophage inflammatory protein–1β (OR 1.72, 95% CI: 1.23 to 2.40), interleukin (IL)-8 (OR 1.50, 95% CI: 1.09 to 2.05), and monocyte chemotactic protein-1 (OR 1.36, 95% CI: 1.01 to 1.83). None of the other 7 cytokines tested predicted HIV risk. Decision tree analyses confirmed this association, with gradients of IP-10, IL-8, and granulocyte-macrophage colony-stimulating factor concentrations correctly classifying 77% of HIV outcomes. Conclusions: Our findings suggest that mucosa-biased gradients of IP-10, macrophage inflammatory protein–1β, IL-8, and monocyte chemotactic protein-1 are associated with an increased risk of HIV infection. Abstract : Supplemental Digital Content is Available in the Text.